2022
DOI: 10.53730/ijhs.v6n2.6728
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the emotional freedom techniques to reducing stress in diabetic patients

Abstract: The research aimed to recognize the EFT effect on the stress reduction of diabetes mellitus patients.  The Research used a quasi-experimental design non-randomization pre-test – post-test group design. The ‘t’ value for stress level before EFT was performed with a p-value of 0,000 and for stress level after EFT p-value was 0,000. From the statistic, it was concluded that there was a significant EFT effect on stress reduction in patients with diabetes mellitus. The Emotional Freedom Technique (EFT) including th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…DR can be prevented with proper screening and treatment for diabetes. [10] Strict glycemic control, early detection and proper treatment are the keys to stopping the progression of the disease [6], [32], [35], [42]. Therefore, the current study was aimed to assess the awareness and KAP of DR patients with T2D in Egypt and Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DR can be prevented with proper screening and treatment for diabetes. [10] Strict glycemic control, early detection and proper treatment are the keys to stopping the progression of the disease [6], [32], [35], [42]. Therefore, the current study was aimed to assess the awareness and KAP of DR patients with T2D in Egypt and Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%
“…Egypt ranked ninth and Saudi Arabia ranked seventh in the top 10 countries among the people with 20-79 year old [5], [11], [19], [24], [31] [32] Diabetic retinopathy (DR) is considered one of the most common and serious complications of DM, is the fifth most common cause of visual impairment in the world, and the 4 th most common cause of blindness [33], [8]. As a result of DR, productivity may decrease, quality of life may deteriorate, and socio-economic burden may increase [31], [34], [35].…”
Section: Significance Of the Studymentioning
confidence: 99%
“…ATP III considered the obesity epidemic is mainly responsible for the rising prevalence of metabolic syndrome. Obesity contributes to hypertension, high serum cholesterol, low HDL, and hyperglycaemia and it is otherwise associated with high cardiovascular disease risk [12,13] Women tend to have fewer cardiovascular events, the populationattributable risk for hypertension is higher for women than men due to their longer life expectancy and the rise in the incidence of hypertension with age. [14] Advancing age affects all levels of pathogenesis which likely explains why the prevalence of MS increases with age.…”
Section: Introductionmentioning
confidence: 99%
“…After the crisis, the capacity of the patient's sera to precipitate with polysaccharide (CPS) rapidly disappeared, and the C-reactive material was not found in sera from normal healthy individuals. [14] Avery and his collaborators characterised the C-reactive material as a protein which required calcium ions for its reaction with CPS and introduced the term 'acute phase' to refer to serum from patients acutely ill with infectious diseases and containing the C-reactive protein. Lofstorm independently described a non-specific capsular swelling reactions of some strains of pneumococci when mixed with acute phase sera and subsequently showed that the substance responsible was CRP.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that concentrations of C-reactive protein is directly correlated with the presence and severity of atherosclerosis and are predictors of coronary events and mortality in patients with acute coronary syndromes. Recently CRP was shown to be a risk predictor for future myocardial infarction, stroke and coronary heart disease death in apparently healthy individuals [14,15]. This potential predictive capacity of CRP warrants further evaluation…”
Section: Introductionmentioning
confidence: 99%